THEORETICAL KNOWLEDGE OF PHYSIOTHERAPISTS ABOUT GERONTOLOGY (Zdravstveni glasnik, 2024)
Introduction: Because population aging is a global issue, healthcare practitioners should be educated in gerontology and work with senior patients. People in their third decade encounter new health challenges, which must be addressed adequately.Objective: To examine the knowledge of physiotherapists about gerontology.Subjects and methods: The research was conducted in August 2023. A questionnaire on general characteristics and a Knowledge Test questionnaire on aging and old age were used to collect data. The sample of respondents consists of 80 employed physiotherapists from Bosnia and Herzegovina. Data processing was performed using Google Forms and Microsoft Office Excel.Results: The average respondent correctly answered 70.31 % of the questions. They had almost the same amount of right answers regardless of whether they had difficulty working with elderly patients or were familiar with active aging programs. The majority of physiotherapists (96.30 %) agree that gerontology should be discussed more in education and that a one-day gerontology workshop would improve the quality of their work with elderly patients (90.00 %).Conclusion: Physiotherapists who participated in the research showed on average, relatively good level of konwledge in the field of gerontology, but there is room for improvement through a workshop in this field, which most respondts agree would improve their work.